Evaluation of Oral Health Promotion and Prevention Service of Contracting Unit of Primary Care in Fiscal Year 2006 - Kongtawelert, Prinya; Wongkongkathep, Sunee (Journal of Health Science of Thailand, 2019)
The study was aimed at (1) describing the pattern of oral health promotion and prevention services in contracting units of primary care (CUP) (2) assessing the performance of Primary Care Unit- Dental nurse in term of oral health outcomes and (3) identifying factors and constraints influencing the service. Data was collected by using a mailed questionnaire sent to dentist-in-charge of every Provincial Health Office, dentists working in 450 hospitals and dental hygienists in 450 Primary Care Units from 75 provinces under the Ministry of Public Health during April - May 2007. Descriptive statistical analysis was used and the results revealed that 64.1 percent of PCUs in 2006 provided no oral health service; 23.5 percent provided service by dental nurses and 12.5 percent extended their service by dental mobile units. Considering basic oral health promotion and prevention service in hospitals and PCUs, 90 percent of the provision was adhered with antenatal clinic,well baby clinic and school health program, whereas no oral health service was delivered in any home visit or chronic care clinic. Main activities included oral examination, health education, toothbrushing exercise and dental care and treatment. Among these activities, dental nurse was the main service provider. Suggestions to improve the oral health service in PCU included strengthening planning for oral health promotion and prevention at local level, adequate budget support, strengthening the information system for management, monitoring and evaluation and then building the health team capacity.